2007
DOI: 10.1016/j.worlddev.2006.08.003
|View full text |Cite
|
Sign up to set email alerts
|

The Trouble with the MDGs: Confronting Expectations of Aid and Development Success

Abstract: The Millennium Development Goals (MDGs) are unlikely to be met by 2015, even if huge increases in development assistance materialize. The MDGs are a set of quantitative, time-bound targets for indicators such as poverty, education and mortality in developing countries adopted unanimously by the UN in 2000. However, the rates of progress required by many of the goals are at the edges of or beyond historical precedent. At the same time, there appear to be limits to the degree to which aid can contribute to devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
115
0
8

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(125 citation statements)
references
References 40 publications
0
115
0
8
Order By: Relevance
“…At present, progress towards MDG-5 is seriously off target. 3,4 Between 1990 and 2005 there was a decline in maternal mortality across Latin America and the Caribbean, with the MMR decreasing from 179 maternal deaths per 100 000 live births to 132 per 100 000, and across Asia, with a decrease from 410 to 329 per 100 000. However, MMRs in sub-Saharan Africa have remained high, at over 900 maternal deaths per 100 000 live births.…”
Section: Introductionmentioning
confidence: 99%
“…At present, progress towards MDG-5 is seriously off target. 3,4 Between 1990 and 2005 there was a decline in maternal mortality across Latin America and the Caribbean, with the MMR decreasing from 179 maternal deaths per 100 000 live births to 132 per 100 000, and across Asia, with a decrease from 410 to 329 per 100 000. However, MMRs in sub-Saharan Africa have remained high, at over 900 maternal deaths per 100 000 live births.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, one should consider economic growth rates: in 2007 the Africa Progress Panel suggested that the region needs an annual GDP growth rate of 7%, up from its existing 5.4% if it is to make "…substantial inroads into poverty reduction" (Clemens, 2007). In fact, an annual growth rate of 5.4% in itself is impressive: should it last until 2015 it would be in the ISSN 1948-5433 2013 top 1/5 of GDP growth rates during the period 1965-2005 for all regions.…”
Section: Research In Applied Economicsmentioning
confidence: 99%
“…Furthermore, the global success in reaching the first MDG can to a large extent be attributed to the tremendous economic development in East Asia over the past two decades (tables 1–4). 3 China alone has made a major contribution to the achievement of MDG 1. However, not much has happened in Africa.…”
Section: Introductionmentioning
confidence: 99%
“…In countries like Kenya, Nigeria and Zambia, the ratio of people living on less than US$1.25 a day has actually increased (table 4). 2 3 This raises the question whether achieving MDG 1 was due to the MDG effort or was just the result of inevitable development as the most populous country on Earth reached a developmental tipping point. This suggestion has both positive and negative implications—positive in the sense that once the economy of a developing society reaches a critical mass the rate of poverty will decrease as a result, and negative in the sense that world community efforts may ultimately be irrelevant as macroeconomics have a dynamic of their own.…”
Section: Introductionmentioning
confidence: 99%